FAMILIRIZATION TRIP OLEH DINAS PARIWISATA DAN KEBUDAYAAN DKI JAKARTA DALAM PENGENALAN MUSEUM TEKSTIL TERHADAP WISATAWAN MANCANEGARA - Sylvia Desianty (UNIVERSITAS STEKOM, 2020)
AbstractThis research is conducted to analyze how the Famtrip strategy is done, the result, and the obstacle. Themethod used in this research is descriptive qualitative using the Nine Steps of Public Relations by RonaldD. Smith to analys the strategy, interview and data research to analys the result and the obstacle. Theresult of this research explains that Famtrip has been done well but in the other hand has not givesignificant result to the increasing number of foreign tourists visiting Jakarta Textile Museum.Keywords: Tourism, Familiarization Trip, Museum Tekstil Jakarta, Strategy.